2015
DOI: 10.1152/ajpregu.00447.2014
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle weakness in the Zucker diabetic fatty rat

Abstract: The obesity epidemic is considered one of the most serious public health problems of the modern world. Physical therapy is the most accessible form of treatment; however, compliance is a major obstacle due to exercise intolerance and dyspnea. Respiratory muscle atrophy is a cause of dyspnea, yet little is known of obesity-induced respiratory muscle dysfunction. Our objective was to investigate whether obesity-induced skeletal muscle wasting occurs in the diaphragm, the main skeletal muscle involved in inspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
0
15
3
Order By: Relevance
“…Preclinical studies of respiratory function in obesity have largely employed genetically obese Zucker diabetic fatty (ZDF) rats. In this model, ex vivo diaphragmatic testing has yielded equivocal results, with contractile force reduced in older animals (8) but unchanged (9,10) or increased (11) in younger animals. ob/ob mice demonstrate hypoventilation reversible by leptin infusion, indicating that this adipokine may regulate central respiratory drive (12).…”
mentioning
confidence: 99%
“…Preclinical studies of respiratory function in obesity have largely employed genetically obese Zucker diabetic fatty (ZDF) rats. In this model, ex vivo diaphragmatic testing has yielded equivocal results, with contractile force reduced in older animals (8) but unchanged (9,10) or increased (11) in younger animals. ob/ob mice demonstrate hypoventilation reversible by leptin infusion, indicating that this adipokine may regulate central respiratory drive (12).…”
mentioning
confidence: 99%
“…To this point, the diaphragm is the primary skeletal muscle for supporting gas exchange and normal respiratory function. Recent data indicate that diaphragm skeletal muscle wasting is involved in inspiration dysfunction in the Zucker diabetic fatty rat (12). In their study in this issue of Diabetes , Buras et al (13) further investigated whether fibro-adipogenic diaphragm remodeling occurs in obesity-associated respiratory impairment and whether FAPs contribute to skeletal muscle dysfunction in a clinically relevant mouse model of high-fat diet–induced obesity and associated respiratory dysfunction.…”
mentioning
confidence: 99%
“…4 The diaphragm is an important skeletal muscle involved in respiration in mammals. 5 A previous study by our group reported that diaphragmatic contractile function significantly declined in streptozotocin (STZ)-induced diabetic rats, and that the mechanism was correlated with excessive oxidative stress and inflammation in diaphragmatic tissue. 6 Moreover, the excessive inflammatory reaction in diabetes often causes collagen deposition and muscle fibrosis.…”
Section: Introductionmentioning
confidence: 96%